Vertical cropping to enhance productivity and profitability of dry terraces in North Eastern Indian Himalayas - PANWAR, A S; BABU, SUBHASH; NOOPUR, KOHIMA; TAHASHILDAR, M; KUMAR, SANJEEV; SINGH, ABHISHEK (The Indian Journal of Agricultural Sciences, 2019)
Land terracing is a vital means to minimize soil erosion in steep slopes of north eastern region of India. Monocropping of turmeric is one of the main production systems in these terraces, resulting in poor land productivity and profitability. Hence, a fixed plot field experiment was undertaken during five consecutive years (2012–17) at ICAR Research Complex for NEH Region, Meghalaya by involving five vertical cropping combinations, viz. turmeric (Curcuma longa)+cucumber (Cucumis sativus), turmeric+bottlegourd (Lagenaria siceraria), turmeric+sponge gourd (Luffa aegyptiaca), turmeric+squash (Sechium edule) and turmeric sole (open cultivation) to find out the best cucurbits for vertical integration with turmeric for efficient utilization of natural resources and profit maximization. Results revealed that integration of bottle gourd with turmeric in vertical fashion recorded the maximum system productivity (33.94 t/ha), profitability (` 1308 ha/day) and B:C ratio (3.37). Over all, vertical integration of cucurbits increased 38.52% yield of turmeric over open cultivation. Maximum enhancement in soil organic carbon (SOC) (2.18%), available N (241 kg/ha), P (22.2 kg/ha) and K (194.7 kg/ha) were recorded when squash was integrated with turmeric followed by turmeric + bottlegourd vertical cropping system. Integration of cucurbits with turmeric improves soil microbial biomass carbon (SMBC) level by 9.85% over the open cultivation of turmeric in dry terraces. Hence, vertical integration of cucurbits with turmeric not only enhances the system productivity and monetary returns of dry terraces but also improves the soil fertility status over open cultivation of turmeric.